PENGARUH PENDIDIKAN SEKSUAL DALAM PEMBELAJARAN TERHADAP PERILAKU KEKERASAN SEKSUAL SISWA KELAS VI - Mimin Ninawati; Sri Lestari Handayani (Universitas Pendidikan Ganesha, 2018)
This study aims to determine whether there is an influence of sex education in learning to the sexual violence behavior of students in 6th grade at SDN Utan Kayu Selatan 23 Pagi, East Jakarta. This research includes quantitative research. The population of this research is 30 students of 6th grade. The sample of this study were taken using a saturated sampling technique. Data collected by questionnaire. The data were analyzed using product moment correlation test and significance test. Through product moment correlation test obtained r value of 0.29. It can be stated that the relationship between sex education and the sexual violence behavior of students has a positive but low relation. The coefficient of determination obtained from the calculation is r2 = 29%. This shows that sex education variable contributes 29% to sexual violence behavior in 6th grade students of SDN Utan Kayu Selatan 23 East Jakarta, while 71% is contribution from other factors such as home environment. From the calculation of significance test coefficient obtained tcount> ttable (1.759 > 1.697), it can be concluded that there is a significant influence between sex education on sexual violence behavior.